Beyond 17% stable perovskite solar module via polaron arrangement of tuned polymeric hole transport layer. (April 2021) - Yaghoobi Nia, Narges; Zendehdel, Mahmoud; Abdi-Jalebi, Mojtaba; Castriotta, Luigi Angelo; Kosasih, Felix U.; Lamanna, Enrico; Abolhasani, Mohammad Mahdi; Zheng, Zhaoxiang; Andaji-Garmaroudi, Zahra; Asadi, Kamal; Divitini, Giorgio; Ducati, Caterina; et al.
Abstract: Operational stability of perovskite solar cells (PSCs) is rapidly becoming one of the pressing bottlenecks for their upscaling and integration of such promising photovoltaic technology. Instability of the hole transport layer (HTL) has been considered as one of the potential origins of short life-time of the PSCs. In this work, by varying the molecular weight (MW) of doped poly(triarylamine)(PTAA) HTL, we improved by one order of magnitude the charge mobility inside the HTL and the charge transfer at the perovskite/HTL interface. We demonstrate that this occurs via the enhancement of polaron delocalization on the polymeric chains through the combined effect of doping strategy and MW tuning. By using high MW PTAA doped combining three different dopant, we demonstrate stable PSCs with typical power conversion efficiencies above 20%, retain more than 90% of the initial efficiency after 1080 h thermal stress at 85 °C and 87% of initial efficiency after 160 h exposure against 1 sun light soaking. By using this doping-MW strategy, we realized perovskite solar modules with an efficiency of 17% on an active area of 43 cm 2, keeping above 90% of the initial efficiency after 800 h thermal stress at 85 °C. These results, obtained in ambient conditions, pave the way toward the industrialization of PSC-based photovoltaic technology. Graphical Abstract: ga1 Highlights: A polaron arrangement was applied for perovskite solar cells via molecular weight tuning and doping strategy. Charge mobility in the HTL and at the perovskite/HTL interface improved by one order of magnitude via polaron arrangement. Reproducible batches of stable PSCs with typical power conversion efficiencies above 20% were realized. Large area perovskite solar modules with an efficiency of 17% on an active area of 43 cm 2 and 730 mW power were fabricated. Highly stable PSCs with more than 1000 h thermal stability at 85 °C and 160 h against 1 sun light soaking were fabricated.